2014
DOI: 10.1590/0103-5150.027.004.ao11
|View full text |Cite
|
Sign up to set email alerts
|

Influence of body weight unloading and support surface during walking of children with cerebral palsy

Abstract: Introduction Partial body weight support (BWS) systems have been employed for gait training of children with cerebral palsy (CP). Therefore, it would be important to analyze if the type of walking surface and the amount of body weight unloading over lower limbs change the way these children walk. Objectives Investigate the influence of walking surface and amount of body weight unloading on the spatial temporal characteristics during walking of children with CP. Materials and methods Seven children with spastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In a subsequent study, 56 we investigated spatiotemporal parameters and joint angles under the same experimental conditions as the previous one. 55 Overall, the second study revealed that even the children who could not walk independently were able to walk with a BWS system on a treadmill and on the ground. More importantly, even though we found a high variability among the children who participated in this study, we observed that children with CP walking with the overground BWS system presented a gait pattern more similar to that presented by typically developing children.…”
Section: The Use Of Partial Bws Systems In Children With Cerebral Palsymentioning
confidence: 96%
See 3 more Smart Citations
“…In a subsequent study, 56 we investigated spatiotemporal parameters and joint angles under the same experimental conditions as the previous one. 55 Overall, the second study revealed that even the children who could not walk independently were able to walk with a BWS system on a treadmill and on the ground. More importantly, even though we found a high variability among the children who participated in this study, we observed that children with CP walking with the overground BWS system presented a gait pattern more similar to that presented by typically developing children.…”
Section: The Use Of Partial Bws Systems In Children With Cerebral Palsymentioning
confidence: 96%
“…52,53 Instead of conducting a gait intervention, we investigated children with CP walking with BWS on a treadmill and on the ground. 54,55,56 Initially, we investigated children with CP with mild motor impairment (independent walkers) walking with 0% and 30% of BWS on a treadmill and on the ground. 54 Spatiotemporal parameters and joint angles were compared among the experimental conditions and free walking.…”
Section: The Use Of Partial Bws Systems In Children With Cerebral Palsymentioning
confidence: 99%
See 2 more Smart Citations
“…Body weight modulation, including providing partial support of a person’s body weight (Celestino et al, 2014; Cherng et al, 2007; Kurz et al, 2011; Phillips et al, 2007; Provost et al, 2007) and addition of external loads (Dodd et al, 2003; McBurney et al, 2003; Simão et al, 2014), is broadly used in research and clinical practice. This method is often adopted for individuals with neurodevelopmental disorders during steady-state gait training (Celestino et al, 2014; Cherng et al, 2007; Kurz et al, 2011; Phillips et al, 2007; Provost et al, 2007; Simão et al, 2014). The evidence is less robust for the effect of body weight modulation on the initiation of stair ascent.…”
Section: Introductionmentioning
confidence: 99%